Expanded bed anion exchange adsorption for the purification of bacteriophage M13 - Shamsu Zaman, Mayamarni (2009)
The filamentous bacteriophage M13 can be used to display foreign peptides and proteins, allowing the construction of theurapeutic, vaccine development, diagnostic and technological tools of broad utility. The current technique used to purify bacteriophage M13 by using conventional method but the long processing time and large unit requirement makes this method not economical. The present work focused on the importance of performing an expanded bed anion exchange adsorption experiments for purification of bacteriophage M13 and to identify the fluidization properties of Streamline DEAE. UpFront FastLineTM20 (ID = 20 mm) column from UpFront Chromatography was used as a contactor and StreamlineTM DEAE ( = 1.2 g/cm3) from GE Healthcare Lifesciences was used as the anion exchanger. 50 mM of Tris buffer at pH 7.5 was used as the quilibration buffer while 2.0 M of NaCl in 50 mM of Tris buffer was used as the elution buffer. The influence of the operational parameters of UpFront FastlineTM 20 was studied and demonstrated that 13.03 mL/min flow rate, bed height H0 = 17.5 cm are optimum conditions for protein released. The dynamic binding capacity of Streamline DEAE for the bacteriophage (M13) was found to be 63 mL adsorbent at velocity of 250 cm h-1. Due to higher density, higher flow rates (200 to 350 cmhr-1) and biomass concentrations (5% to 20% ww/v) could be applied on expanded bed adsorption. The developed breakthrough curve was measured at different bed height and different biomass concentrations. The accuracy of the model predictions was improved by employing information on the axial variations in the bed voidage, liquid phase axial dispersion and dynamic binding capacity for the experiment. Breakthrough curves for bacteriophage M13 were compared and the process was more efficient at a bed expansion degree of 2.0 (bed voidage of 0.7). The performance of two methods were evaluated and analyzed. Purification of the M13 bacteriophage by precipitation, centrifugation and microfiltration yielded a low recovery percentage (36.07%) but with high purity while purification of the M13 bacteriophage by expanded bed anion exchange adsorption yielded a high recovery percentage (82.86%) but with low purity. Additionally, the total processing time of the expanded bed adsorption process has been shortened by 8 times compared to that of the conventional method.